Barneansvarliges rolle, knyttet til barn som er pårørende til foreldre med psykiske lidelser - en fenomenografisk studie - Ann-Kjærsti Svalheim; Anne Kjersti Myhrene Steffenak (Septentrio Academic Publishing, 2016)
Child-responsible role, related to children as caregivers of parents with mental illness - a phenomenographic study Children as caregivers of parents with mental disorders are a vulnerable group. They have been invisible to service providers until recent years. These children have an increased risk of developing behavioral problems and impaired psychosocial functioning. In 2010, law amendments require that special health have child-responsible personnel, to ensure children and their families proper measures. There is little knowledge of how this role works. The purpose of this study is to uncover the perceptions child-responsible personnel have of their own role.The study is qualitative with a phenomenographic approach. Child-responsible personell have a special interest in working with young caregivers. They act as "watchdog" for colleagues and they provide guidance for parents. Follow-up of children is random where responsibilities are added to therapists. Child-responsible personnel collaborate with municipality, and public health nurse is specifically mentioned. There is still a way to go before the role works as intended.